New Research Instruments Manufactured by Shimadzu Corporation - Sukhomlinov, A.B. (Science and Innovation, 2024)
The paper deals with new models of research instruments manufactured by Japanese corporation SHIMADZU, including liquid and gas chromatographs, mass spectrometers, IR spectrophotometer, energy dispersive X-ray spectrometers, particle size analyzer, and micro hardness tester. The special attention has been paid to enhancement of performance specifications.